Relationship between Activity of Changing Underwear and Spinopelvic Parameters after Surgery for Adult Spinal Deformity - Suzuki, Teppei; Yamanouchi, Yoshinobu; Kurakawa, Takuto; Yamamoto, Shuji; Ryu, Masao; Matsuo, Tomoya; Kawakita, Kohei; Ito, Masaaki; Uno, Koki; Terao, Takashi (Journal of Spine Research, 2021)
Introduction: In activity of daily living (ADL), changing underwear is one of the problem after adult spinal deformity (ASD) surgery. However, few reports have evaluated the factors. We performed this study to investigate the relationship between activity of changing underwear and spinopelvic parameters after surgery.Methods: We reviewed 111 patients (75 females, average 70-year at the surgery) who underwent fixation surgery from lower thoracic spine down to pelvis for ASD. Patients were divided into independent group and requiring assistance group, according to the degree of self-reliance of dressing activities after surgery. X-ray parameters (SVA, TK, LL, PT, SS, PI, PT-LL) and preoperative ROM of hip joint were compared between two groups.Results: UIV were T10 in 95 patients, S2 alar-iliac screws were used in all cases, and interbody fusion at L5/S1 were performed in 88 cases. Mean spinopelvic parameters (independent group/requiring assistance group) which SVA (28 mm/34 mm), PT (25°/39°) preoperatively, and PT (18°/24°) postoperatively were significantly different between two groups (p <0.01). However, preoperative ROM of hip joint was not significantly different.Conclusions: Postoperative pelvic tilt was significantly smaller in patients with independent activity of changing underwear than in patients requiring assistance, that suggested flexion of the hip joint might allow body trunk to lean forward more deeply. Preoperative intervention to improve mobility of hip joint will be required to rehabilitation for adult spinal deformity patients, especially with severe deformity.